2005
DOI: 10.1007/s11064-005-6787-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Genes in Transgenic Mice Carrying Human Mutant Presenilin-2 (N141I): Correlation of Selenoprotein M with Alzheimer’s Disease

Abstract: Mutations in genes for Alzheimer's disease (AD) result in a modulating of gene expressions in the brains of patients with AD. The aim of this study was to identify genes whose expression is modulated due to the over-expression of human mutant presenilin-2 (N141I) (hPS2m) in transgenic mice, which has previously been produced by us. To test this, GeneFishing DEG101 technique was performed on large-scale screen of mRNA from transgenic and non-transgenic brains. A total of 40 transcriptional products correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
(35 reference statements)
0
33
0
1
Order By: Relevance
“…M. Muller et al (9) showed that this protein plays a major role in spicule formation in the demosponge Suberites domuncula. In addition, Hwang et al (10) suggested that SelM might play a suppressive or protective role in the pathology of patients with Alzheimer's disease. However, no transgenic rat expressing human SelM under the control of the human cytomegalovirus (CMV) immediate early promoter has been available for use in the study of the function of SelM in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…M. Muller et al (9) showed that this protein plays a major role in spicule formation in the demosponge Suberites domuncula. In addition, Hwang et al (10) suggested that SelM might play a suppressive or protective role in the pathology of patients with Alzheimer's disease. However, no transgenic rat expressing human SelM under the control of the human cytomegalovirus (CMV) immediate early promoter has been available for use in the study of the function of SelM in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study of transgenic mice overexpressing the human mutant gene presenilin-2 associated with familial Alzheimer disease found that SelM expression was significantly down-regulated, suggesting a potential neuroprotective function for SelM in the prevention of Alzheimer disease (24). Familial Alzheimer disease-linked presenilin-2 mutations have been observed to alter intracellular calcium homeostasis (25), and more recently presenilin-2 was shown to modulate calcium shuttling between the endoplasmic reticulum and mitochondria (26).…”
Section: Discussionmentioning
confidence: 99%
“…6D). No significant differences in average weekly food consumption were found for either genotype (F (1,24) ϭ 1.253, p Ͼ 0.05) or gender (F (1,24) ϭ 0.04904, p Ͼ 0.05). However, the two animals that consumed the most food during this 4-week period were female SelM KO mice.…”
Section: Normal Brain Morphology and Density Of Parvalbumin (Pv) Intementioning
confidence: 91%
See 1 more Smart Citation
“…In mouse, SelM is moderately expressed in various tissues including the heart, lung, kidney, uterus, and placenta, and highly expressed in thyroid and brain (180). Interestingly, overexpression of the presenilin-2 (PS2) gene responsible for the early-onset Alzheimer's disease caused the suppression of SelM, but not SelP, in the brain of transgenic mice (152). Detailed studies of SelM in the brain are required to establish its function and potential involvement in disease.…”
Section: J Selenoprotein Mmentioning
confidence: 99%